Pengaruh Investasi Swasta, Infrastruktur Jalan, dan Belanja Modal Pemerintah terhadap Pertumbuhan Ekonomi di Provinsi Kalimantan Selatan Tahun 2006-2021 - Hermawan, Agus; Yunani, Ahmad (PPJP ULM, 2023)
This study aims to know the Effect of Private Investment, Road Infrastructure, and Government Capital Expenditure simultaneously on Economic Growth in South Kalimantan Province from 2006 to 2021 and Know which factors significantly influence Economic Growth in South Kalimantan. South Kalimantan Province in 2006-2021. Data collection techniques in research using Documentation Techniques. The analysis technique uses multiple linear regression analysis techniques with Eviews 10 software. This study found that the variables of private investment, road infrastructure, and the authorities' capital expenses significantly impact economic growth in Kalimantan Province. For the 2006-2021 period, private investment became the most dominant variable in its influence on economic growth in South Kalimantan Province for the 2006-2021 period.